Predictors of reputation through university social responsibility practices in a Malaysian private university: the customer’s perspective - Chan, Tak Jie; Hon, Tat Huam (Penerbit Universiti Kebangsaan Malaysia, 2019)
Social responsibility has emerged tremendously as an important field of study in the past decades. Institutions today have realised the significance of being ethical in their operations in order to attract various stakeholders, especially the customers. However, majority of the past studies on social responsibility mainly focus on big corporations, while the influence of social responsibility practices in university remains understudied. The purpose of this study was to examine the predicting factors of University Social Responsibility (USR) practices and reputation from the students’ viewpoint on one of the private higher educational institutions in Malaysia. A survey method was employed using multistage sampling. Questionnaires were distributed and generating 400 valid responses. The data were then analysed using Pearson-Product Moment Correlation and Multiple Regression test (enter method) through the Statistical Package for the Social Sciences (SPSS) version 25.0. Based on the findings, all the seven USR dimension, namely operational responsibility, stakeholder’s (student) responsibility, university-firm relationship, legal responsibility, environmental values, philanthropy responsibility, and community engagement yielded positive and moderate relationships with reputation. In addition, multiple regression analysis showed that operational responsibility, university-firm relationship, legal responsibility, philanthropy responsibility, and community engagement were the significant predicting factors that can enhance reputation in the current context. Conclusion, limitations of the study, implications of the findings, and suggestions for future study are also discussed.